Plasma proteomic analysis reveals key pathways associated with divergent residual body weight gain phenotype in beef steers - Idowu, Modoluwamu; Taiwo, Godstime; Sidney, Taylor; Adewoye, Anjola; Ogunade, Ibukun M. (Frontiers in Veterinary Science, 2024)
We utilized plasma proteomics profiling to explore metabolic pathways and key proteins associated with divergent residual body weight gain (RADG) phenotype in crossbred (Angus × Hereford) beef steers. A group of 108 crossbred growing beef steers (average BW = 282.87 ± 30 kg; age = 253 ± 28 days) were fed a high-forage total mixed ration for 49 days in five dry lot pens (20-22 beef steers per pen), each equipped with two GrowSafe8000 intake nodes to determine their RADG phenotype. After RADG identification, blood samples were collected from the beef steers with the highest RADG (most efficient; n = 15; 0.76 kg/d) and lowest RADG (least efficient; n = 15; -0.65 kg/d). Plasma proteomics analysis was conducted on all plasma samples using a nano LC-MS/MS platform. Proteins with FC ≥ 1.2 and false-discovery rate-adjusted P-values (FDR) ≤ 0.05 were considered significantly differentially abundant. The analysis identified 435 proteins, with 59 differentially abundant proteins (DAPs) between positive and negative-RADG beef steers.Plasma abundance of 38 proteins, such as macrophage stimulating 1 and peptidase D was upregulated (FC ≥ 1.2, FDR ≤ 0.05) in positive-RADG beef steers, while 21 proteins, including fibronectin and ALB protein were greater (FC < 1.2, FDR ≤ 0.05) in negative-RADG beef steers.The results of the Gene Ontology (GO) analysis of all the DAPs showed enrichment of pathways such as metabolic processes, biological regulation, and catalytic activity in positive-RADG beef steers. Results of the EuKaryotic Orthologous Groups (KOG) analysis revealed increased abundance of DAPs involved in energy production and conversion, amino acid transport and metabolism, and lipid transport and metabolism in positive-RADG beef steers. The results of this study revealed key metabolic pathways and proteins associated with divergent RADG phenotype in beef cattle which give more insight into the biological basis of feed efficiency in crossbred beef cattle.